The treatment of transarterial chemoembolization/hepatic arterial infusion chemotherapy combined with lenvatinib and PD-1 inhibitor is effective against hepatocellular carcinoma with portal vein tumor thrombus: A systematic review - Yuanren, Gao; Yin, Linan; Liu, Ruibao; Cui, Yali (Frontiers in Oncology, 2023)
Objective Lenvatinib combined with programmed cell death protein-1 (PD-1) inhibitor has achieved good survival results in the treatment of hepatocellular carcinoma with portal vein tumor thrombus. Transarterial chemoembolization (TACE) or hepatic arterial infusion chemotherapy (HAIC) has attracted attention because of its high response rate and favorable survival rate in patients with liver cancer and portal vein tumor thrombus. This study aimed to compare the efficacy and safety of Lenvatinib combined with PD-1 inhibitor plus TACE or HAIC in patients with hepatocellular carcinoma with portal vein tumor thrombus. Method We searched PubMed, Embase and the Cochrane Library for studies. These included randomized controlled trials (RCTs) or clinical trials of Lenvatinib plus PD-1 inhibitor plus TACE or HAIC (intervention group) versus Lenvatinib plus PD-1 inhibitor or Lenvatinib plus TACE/HAIC or Lenvatinib alone (control group) in liver cancer with portal vein tumor thrombus The primary outcomes were overall survival and progression-free time, and the secondary outcomes were response rate and the rate of adverse events. According to the heterogeneity among different studies, Revman5.4 was used to conduct fixed effect or random effect model analysis. Results Five clinical trials were included, including 311 cases in the intervention group and 309 cases in the control group. In terms of efficacy, compared with the control group, the overall survival (HR=1.88, 95%CI: 1.57-2.25, P < 0.00001) and progression-free (HR=1.62, 95%CI: 1.41-1.86, P < 0.00001), better efficacy, and better disease response than the control group. In terms of safety, the risk of treatment-related adverse events in the intervention group was higher than that in the control group, and White Blood cell count decreased (RR=0.72, 95%CI: 0.38-1.37, P=0.32), Platelet count decreased (RR=0.99, 95%CI: 0.65-1.51, P=0.96) and Total bilirubin increased (RR=0.86, 95%CI: Increased) 0.88-1.28, P=0.46) were lower than those in the control group, and the rest were higher than those in the control group, and the differences in some results were statistically significant. Conclusions TACE or HAIC combined with Lenvatinib plus PD-1 inhibitor can effectively delay the progression, prolong the survival period and improve the quality of life of liver cancer patients with portal vein tumor thrombus.